THE ISLAMIC FEMINISM: A Methodological Reconstruction of Contemporary Islamic Era - Chusnul Chotimah; Arifah Millati Agustina (AL-TAHRIR, 2019)
Abstract: Feminism always be a favorable discussion among academics. It is supported by the increasing blending of non-dichotomous intellectual and study area, between the pure-Islamic studies and anti-Islamic studies. The studies were started to be integral since the 19th century marked by the emergence of the various Islamic studies. Muslim scholars have conducted research on women from various perspectives, family-law, and humiliation in the society. The study of women has attracted attention of international Muslim scholar that respond to the methodological reconstruction. It occurred due to the concern of women existence especially for women who require a distinct protection. This paper employed a historical-methodological approach which analysed the views of two Muslim scholars which are well-known with western education and concern about women’s issues, namely Khaled Abou el Fadl who reviewed the notes on the fatwa of the middle eastern scholars at the CRLO institutions (council for scientific research and legal opinion) and Ziba Mir Hosseini who studies about the sacredness and profanity of Islamic law, especially the position of women in family law.الملخص: إن الحديث عن المساواة بين الجنسين حديث جذّاب عند الأكاديميين. هذا الواقع مؤيّد بارتقاء  الثقافة الأكاديمية وعدم التفريق بين الدراسات الإسلامية المحضة وما في خارجها. بدأ أن اتّحدت العلوم في القرن التاسع عشر بظهور أنواع العلوم الإسلامية. ثمة من العلماء المسلمين قاموا بالدراسات عن النساء من وجهات نظر متعددة بداية من مكانتها في فقه الأحوال الشخصية، ووصمة عار المجتمع، بل وإن الدراسات عن النساء تثير اهتمام الخبراء المسلمين في المستوى العالمي وتدفعهم إلى إعادة البناء المنهجي. هذه الحالة نوع من اهتمام الخبراء المسلمين تجاه النساء لكونهن في حاجة إلى الرعاية الخاصة ولكثرة الحديث عن وجودهن. استخدم هذا المقال المدخل التاريخي المنهجي ويناقش رأي العالمين المسلمين المعاصرين الكائنين في لب التربية الغربية ومهتمين تجاه قضايا النساء ( خالد أبو فضل وزبا مر حسين) . انتقد خالد الفتاوى التى أصدرها علماء الشرق الأوسط في مؤسسة  CRLO (council for scientific research and legal opinion)  ، وزيبا قامت بدراسة قدسية الأحكام الإسلامية، خاصة مكانة المرأة في فقه الأحوال الشخصية.Abstrak: Feminisme merupakan kajian kontemporer yang selalu hangat dibicarakan di tengah-tengah insan akademik. Hal ini didukung oleh semakin meningkatnya budaya intelektual dan wilayah kajian yang non dikotomis, antara kajian Islam murni dengan pengetahuan di luarnya. Keilmuan mulai bersifat integral sejak abad ke-19 yang ditandai dengan munculnya berbagai keilmuan Islam. Banyak intelektual Islam yang melakukan penelitian tentang perempuan dari berbagai sudut pandangnya, mulai kedudukannya dalam hukum keluarga, stigma masyarakat, bahkan kajian mengenai perempuan menyita perhatian Muslim scholar Internasional yang menciptakan respon Muslim scholar kontemporer untuk melakukan rekonstruksi metodologis. Tindakan ini adalah bentuk kepedulian Muslim scholar terhadap perempuan yang keberadaannya banyak diperbincangkan dan memerlukan perlindungan khusus. Artikel ini dengan menggunakan pendekatan historis-metodologis mengulas pandangan dua intelektual Islam kontemporer yang berjibaku dengan pendidikan Barat, dan konsen terhadap isu-isu perempuan, yaitu Khaled Abou el Fadl yang memberikan catatan terhadap fatwa Muslim scholar Timur Tengah dalam lembaga CRLO (council for scientific research and legal opinion) dan Ziba Mir Hosseini yang melakukan kajian sakralitas dan profanitas hukum Islam, terutama kedudukan perempuan dalam hukum keluarga.